Differences in Self-Concept of Teenagers Judging from the Use of the TikTok Application - Wattimena, Iryane Marlin (Budapest International Research and Critics University, 2022)
The increasing number of TikTok social media users among teenagers in Indonesia certainly affects one of the stages of adolescent development, namely regarding self-concept. Having a self-concept is very important because a teenager will be able to assess himself and do a job effectively in his life. This study aims to determine the differences in adolescent self-concept in terms of the use of the TikTok application. This research uses quantitative with sampling technique using the methoda comparative approach to compare the presence of one or more variables in two different samples. Participants in this study amounted to 152 teenagers with an age range between 15-18 years and who are users of TikTok or who do not use TikTok. The results of the calculation of the difference test obtained a T-test value of -0.054 and a df (degree of fredoom) value of 150, with sig. = 0.957 (p>0.05). This shows that there is no significant difference in the self-concept of adolescents who do not use the TikTok application with adolescents who use the TikTok application.